KONTRIBUSI KEMAMPUAN DISPOSISI MATEMATIS SISWA SMP DI KABUPATEN BANDUNG BARAT TERHADAP HASIL BELAJAR MATEMATIKA DALAM MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINIER SATU VARIABEL - Ai Siti Nurhayati; Iis Asriah Nurfalah; Luvy Sylviana Zanthy (IKIP Siliwangi, 2020)
This research aims to know how much the mathematical disposition ability of junior high school students in West Bandung Regency contributes to mathematics learning achievement in the material of equations and one variable linear inequality. The data collection was done by giving a questionnaire and analyzing students’ achievement from daily test scores in the material of equations and one variable linear inequality. The population of this research were seventh grade students in West Bandung Regency, with the selected sample by using simple random sampling technique are 25 students of class VII-F in SMP Negeri 1 Gununghalu. Meanwhile, the disposition questionnaire was made based on following indicators; (1) self-confidence (2) persistence or perseverance (3) open thinking or perseverance (4) interest and curiosity (5) monitor and reflect (6) Respect the usefulness of mathematics. The results showed that there was a significant linear relationship between mathematical disposition and student learning achievement, with a contribution of mathematical disposition of 13.8% to student learning achievement on the material equation and one variable linear inequality, and 86.2% influenced by other variables.